Medication overuse headache and its specific clinical markers - Barrientos, Nelson U.; Salles , Philippe G.; Milán , Anna S.; Meza , Paulina C.; Juliet , Raúl P.; Rapoport, Alan (Headache Medicine, 2016)
Introduction: Clinical markers of medication overuse headache (MOH) are based on headache classification developed by the International Headache Society (IHS). This classification include only two criteria: 1) frequency of headache must be 15 or more days per month for at least three or more months; 2) the number of days of overuse medication must be either 10 or 15 days per month depending on the type of medication. However, patients often present with associated clinical markers that are overlooked by most physicians at the first visit. Methods: This is a prospective, longitudinal and observational study of 76 patients admitted to DIPRECA´s hospital Headache Unit. They were all diagnosed with MOH according to the criteria established by the his ICHD III beta. Patients were given standard therapeutic approach that included detoxification, prescription of preventative medications and a standardized follow-up of 6 months. Symptoms of interest were recorded at each appointment and Zung, MIDAS and HIT-6 (headache impact test) scales were applied. Results: Overused medications included nonsteroidal anti-inflammatory drugs (NSAIDs), triptans and ergots. The most significant associated features were headache at awakening, awaking by headache, attentional difficulties, depression, cervical pain and myofascial pain syndrome. All symptoms improved with therapy as well as MIDAS and HIT-6 scores. Discussion: In evaluating patients with MOH consider both the ICHD III beta diagnostic criteria and the common and specific symptoms seen in most cases of MOH.